مقاصد الأسرة عند الشيخ الطاهر بن عاشور :bدراسة فقهية تحليلية في ضوء الواقع المعاصر /cإعداد، حنيفة بنت موسى فتح الله هارون - Hanifah binti Musa Fathullah Harun (Kulliyyah Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2009)
This study addresses in general the Maqasid issue in the Islamic jurisprudence and in particular Maqasid related to family matters as viewed by one of the great scholars of Maqasid: Ibn 'Asyur. The first chapter of the study is dedicated to his educational background that would later shape his scholarly views. The concept of Maqasid and its importance in Ijtihad would also be discussed in this chapter. The second chapter studies the concept of family in Ibn 'Asyur's view through explaining the rights of its members and their responsibilities. The third chapter discusses about family relations and their significance in maintaining the family in the context of the Maqasid. This chapter is concluded by discussing the necessary ways to maintain these relations. The study is done using inductive method in collecting the relevant texts which are later analyzed and criticized in the light of Maqasid al-Shariah and according to Ibn 'Asyur views; and will be studied in relation to the current context while practices which are not in lieu with Islamic teachings will be critically examined.